ANALISIS NORMA SOSIOMATEMATIK DALAM PEMBELAJARAN KOLABORATIF POKOK BAHASAN PERSAMAAN LINIER SATU VARIABEL KELAS VII-B SMP NEGERI 4 JEMBER - Rofiq, Anita Nur; Hobri, Hobri; Setiawan, Toto Bara (Department of Mathematics Education , University of Jember, 2017)
Abstract. Sociomathematical norms is a rule applied when the process of interaction during the learning of mathematics takes place. Collaborative learning is a group learning where students of various variations in both ability and background work together to interact and learn together to improve the understanding of each member. This study aims to describe the implementation of learning mathematics implementation using collaborative learning model and describe sociomathematical norms in collaborative learning in linear equations one variable topic at VII-B of Junior High School 4 Jember. Indicator of sociomathematical norms in this research is elaborated based on mathematic communication ability and social skill of student in collaborative learning. The type of this research is qualitative descriptive research. The instrument of data collection used is learning tool which include RPP, LKS, observation sheet of learning implementation, observation sheet of sociomatic norms in collaboration activity, and interview guide. Based on the results of the study, 26 out of 35 study subjects had positive confidence categories (P1, P2, and P3) on collaborative activities and had an average percentage of sociomathematical norms, 22 very good students, 12 good students and 1 student were good enough. Keywords : Sociomathematical Norms, Collaborative Learning, Student's Belief, Math Communication, Social Skill.